2002
DOI: 10.1016/s0272-6963(01)00078-x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of purchasing team usage in the supply chain

Abstract: Increased attention on supply chain management has highlighted the pivotal role that supply chain management and purchasing teams can play in the overall competitiveness of many firms. This paper presents findings from an exploratory study that analyzes the impact of purchasing’s strategic role, industry context and purchasing organizational structure, on the use of various forms of purchasing teams. Using survey data from a broad sample of industries, we found that team usage was a two‐dimensional construct: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 25 publications
0
69
1
Order By: Relevance
“…The difference might be caused by legal regulations, which require that public funds have to be spent transparently and which necessitate a formal and complex public purchasing process. Johnson, Leenders and Fearon (1998a) and Johnson, Klassen, Leenders, and Fearon (2002) studied the structure of purchasing in service and manufacturing industries and found that service firms are more often centralized than manufacturing companies and that purchasing teams that involve customers prevail in the service industry. In contrast, manufacturing companies have a stronger tendency to (partially) decentralize their purchasing activities and use purchasing teams solely made up of members of the organization.…”
Section: Bur -Business Research Official Open Access Journal Of Vhb Gmentioning
confidence: 99%
See 2 more Smart Citations
“…The difference might be caused by legal regulations, which require that public funds have to be spent transparently and which necessitate a formal and complex public purchasing process. Johnson, Leenders and Fearon (1998a) and Johnson, Klassen, Leenders, and Fearon (2002) studied the structure of purchasing in service and manufacturing industries and found that service firms are more often centralized than manufacturing companies and that purchasing teams that involve customers prevail in the service industry. In contrast, manufacturing companies have a stronger tendency to (partially) decentralize their purchasing activities and use purchasing teams solely made up of members of the organization.…”
Section: Bur -Business Research Official Open Access Journal Of Vhb Gmentioning
confidence: 99%
“…The relationship was analyzed by Johnson, Leenders, and Fearon (1998b) and Johnson, Klassen, Leenders, and Fearon (2002), who studied the degree of centralization as a determinant of the use of different purchasing techniques and the strategic impact of purchasing on the company. Their results indicate that centralized purchasing departments exert a higher influence on major corporate activities than decentralized departments and consequently enjoy a higher strategic role.…”
Section: Bur -Business Research Official Open Access Journal Of Vhb Gmentioning
confidence: 99%
See 1 more Smart Citation
“…Environment is defined as the aggregate of factors that have an impact or the potential to have an impact on an organisation's functioning (Emery and Trist 1965;Thompson 1967). The choice of uncertainty as the sole input variable is predicated on the co-alignment and contingency theories which both play an important role in organisational and operations management research (Hofer 1975;Carroll 1993;Johnson et al 2002).…”
Section: Dea Input Variable -Environmental Uncertaintymentioning
confidence: 99%
“…6 The choice of uncertainty as the input variable in the reference model is predicated on the coalignment and contingency theories of management. Both theories play an important role in organisational research (Carroll 1993;Johnson et al 2002). Van der Vorst and Beulens (2002) pointed out that the literature unanimously recognises that uncertainties in supply, process and demand have a major impact on the manufacturing function.…”
Section: Introductionmentioning
confidence: 99%